Representation Type of Nodal Algebras of Type D - Drozd, Yu. A.; Zembyk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We establish the representation types (finite, tame, or wild) of nodal algebras of type D.